The role of male partner in utilization of maternal health care services in Ethiopia: a community-based couple study - Bedru Hussen Mohammed; Janice Mary Johnston; Dana Vackova; Semira Mehammed Hassen; Huso Yi (BMC, 2019)
Abstract Background Ethiopia has recorded substantial progress in maternal health recently. However, poor utilization of maternal health care services is challenging further improvement. Although male partners are decision-makers in households, the impact of their involvement on maternal health care services has not been well studied. Thus, the objective of this study was to examine the association between male partners' involvement in maternal health care on utilization of maternal health care services. Methods A community-based cross-sectional study was conducted on male/female couples with a baby less than 6 months old (N = 210) in Addis Ababa, Ethiopia. The main independent variable of the study was male partners' involvement in maternal health care. Two structured questionnaires were used to collect the data from men and women. Bivariate and multivariate logistic regression models were used to examine the relationship between the dependent and independent variables. Results Mean age in years was 28.7 (SD = 5.4) for women and 36.2 (SD = 8.8) for men. Half of the men (51.4%) have accompanied their partner to antenatal care (ANC) at least once. However, only 23.1% of them have physically entered the ANC room together. Overall involvement of male partners was poor in 34.8% of the couples (involved in two or fewer activities). After controlling for other covariates, the odds of having 1st ANC visit within the first trimester of pregnancy and skilled delivery attendant at birth were higher in women whose male partners took time to know what happened during ANC visits (AOR = 1.93; 95%CI = 1.04-3.60; AOR = 2.93; 95%CI = 1.24-5.6.90, respectively). Similarly, the odds of having at least one ANC visit, first ANC visit within twelve weeks, HIV testing, skilled birth attendant, and birth in a health facility were higher in couples with higher overall male partner involvement. Conclusion The study demonstrated significant associations between male partners' involvement in maternal health care and utilization of some maternal health care services by female partners.